Enrichment of Tropical Moist Deciduous Forests by Planting in Andaman Islands - Sharma, S. K. (Indian Forester, 1979)
The definition of enrithment planting and the rensons tor adoption or this method have been given the role of enrichment plating in filling the gaps in the regeneration areas with the desired species under selection system and Irregular shelterwood syatem has been highlighted A review of work dOne on enrichment planting in Nigeria, erstwhile French West African colouies of the Ivory Coast, Cameroons, Belgian Congo, British Uganda, Malaya and is India has been furnished. A historical background of the adoption of enriebment planting in Andamaa Islands from the year 1906 uptodate as prescribed in varioas Working Plans has been shren. The environmental factors under which described. The methods employed for earichment the moist deciduous forests in Andaman Isands with Teak and Padauk have been narrated. The statistics of beight and girth of Teak planted in the enrichment areas and Teak growan in plantations of the same age bave been collected and tahulated Curve. I and II depicting the average crop girth by age aad aveage crop beight by age have been drawn. The tentative inferences drawn from these two curves have also been indicated. The expectsion of yield from enrichment plantiog ares in Andaman Islandss has been estimated at 56 Cu m per hectare from Teak and 87 cu m per hectare from indigenous commercially valuable species the regeneration of teak in 1957 enrichment plantaion area in Swamp Island in North Andaman Division bas been pointed out. The esseutial condition. for success and limiting factors for enrichment planting with feak have been discussed. The advantages claimed for enrichment planting have be touched upon It has been concluded that enrichment planting with Teak can be successfully adopted as a normal divisional practice in AnJaman Islands to improve the stocking, economic value of the forests and also for incorporating Teak in the natural, vegetative complex.